Pancreas Cancer-Associated Polymyositis of the Legs Regressing After Cephalic Duodenopancreatectomy: Case Report and Review of the Literature - Amroun, Koceila Lamine; de Mestier, Louis; Deguelte-Lardiere, Sophie; Diebold, Marie-Danièle; Bouché, Olivier; Kianmanesh, Reza (JOP. Journal of the Pancreas, 2012)
Context Inflammatory myopathy, such as polymyositis, has been widely reported as paraneoplastic syndrome associated with various malignancies. However, its association with pancreas adenocarcinoma is very uncommon. Case report A case of a patient with paraneoplastic polymyositis of both legs associated with pancreatic adenocarcinoma is reported here. The diagnosis of polymyositis was highlighted by MRI and confirmed by histopathological examination. The surgical resection of the primary tumor led to the complete resolution of polymyositis with no further recurrence despite later metastases. Conclusion The association between pancreatic cancer and paraneoplastic polymyositis is very uncommon and has to be recognized by clinicians. Image: MRI (T1) axial section of thigh with gadolinium injection.